Strategi Ekspansi PT. Garuda Indonesia Tbk melalui Kolaborasi Internasional dengan SkyTeam Airline Alliance - Ni Made Citra Kusuma Dewi (Jurnal Hubungan Internasional, 2019)
On March 5th 2014, Garuda Indonesia officially joined SkyTeam AirlineAlliance and became the first Indonesian airline that takes part in theglobal airline alliance. Based on that case, the author aims to explore theexpansion strategy of PT. Garuda Indonesa Tbk. through its membershipin SkyTeam. The author will utilize the strategic alliance theory of InternationalBusiness in understanding the relation between Garuda Indonesiaand SkyTeam. The author will also provide several datas to comparethe business operation of PT. Garuda Indonesia before and after joiningSkyTeam Airline Alliance in order to analyze the impact of this alliance.According to the collected data, the author found that the membership ofGaruda Indonesia in SkyTeam has shown positive impacts to the airline’snumber of international traffic, total operating revenues, as well as itsquality of service. Therefore, the author argues that SkyTeam AirlineAlliance contributes not only to the increase of profit earned by GarudaIndonesia, but also the airline’s quality of service.